Dukungan Suami dalam Pemberian ASI Berhubungan Erat dengan Motivasi Menyusui Eksklusif pada Ibu - Endar Timiyatun; Eka Oktavianto (STIKes Surya Global Yogyakarta, 2018)
Exclusive breastfeeding is one program that is quite difficult to develop because it deals with various problems in social society. Until now exclusive breastfeeding coverage in Yogyakarta still has not reached the target expected. The factors that are suspected in this case is lack of exclusive breastfeeding motivation.One cause of this is husband support. The objective of this study was to analyze the relationship between husband’s support in giving brestfeeding and breastfeeding self-efficacy with mother’s exclusive breastfeeding motivation in Puskesmas Sewon II Bantul. The method of this research used non-experimental research with cross-sectional design. Respondents in this study were breastfeeding mothers who had infants 6 months in the work area at Puskesmas Sewon II Bantul. The sampling technique used purposive sampling. The analytical test which was used was to know the relationship of chi-square test. The result was Husband's support for breastfeeding in the working area of Puskesmas Sewon II Bantul Yogyakarta was in the category of 47 people (58.8%). Motivation of exclusive majority breastfeeding mother in moderate category as many as 49 people (61.2%) and breastfeeding self-efficacy has middle category was 56 people (70%) .The result of correlation test between two variables got each p value 0.05. The conclusion was there was a relationship between husband’s support in breastfeeding with exclusive breastfeeding and mother’s exclusive breastfeeding motivation in Puskesmas Sewon II Bantul (p0.05).